Transnasal Humidified Rapid-Insufflation Ventilatory Exchange for Elective Laryngeal Surgery During Pregnancy: A Case Report. Issue 11 (1st December 2019) - Kowalczyk, John J.; Carvalho, Brendan; Collins, Jeremy
Abstract : Transnasal humidified rapid-insufflation ventilatory exchange (THRIVE) maintains oxygenation and blunts the partial pressure of carbon dioxide (PaCO2 ) rise in nonpregnant subjects during apnea. Physiologic changes of pregnancy may attenuate the utility of THRIVE. We present a nulliparous patient at 31 weeks' gestation undergoing tracheal dilation requiring general anesthesia without intubation utilizing THRIVE. Our data confirms prior reports in nonpregnant patients showing markedly extended time to desaturation. However, PaCO2 rise more closely mirrors classic apneic oxygenation in nonobstetric patients. The PaCO2 elevation and subsequent acidosis may limit the utility of THRIVE for prolonged apnea in pregnant surgical patients.